Gauging E-Government Evolution in EU Municipalities - Lourdes Torres; Vicente Pina; Basilio Acerete (Journal of Systemics, Cybernetics and Informatics, 2005)

(untitled)
Since the late 1990s, governments at all levels have launched electronic government projects aimed at providing electronic information and services to citizens and businesses. Although websites are becoming essential elements of modern public administration, little is known about their effectiveness. The objective of this paper is to study the quality and usage of public e-services to citizens in Europe. According to the results of this study, e-government seems to be following a more or less predictable development pattern ranging from a stage in which interaction is limited to what is shown on the screen to stages in which there is two-way communication and service and financial transactions can be completed with a satisfactory level of protection of personal privacy. At present, e-government in almost all the cities studied is merely an extension of the government, with potential benefits in speed and accessibility 24/7. Despite the limited degree of development observed, online access has advantages that are impossible to replicate offline. Even though few expect e-government to completely replace traditional methods of information, e-government is becoming a powerful tool of transformation, which has become embedded in the culture and in the agenda of the public sector.